Customer concentration and exploratory innovation: the mediating effect of perceived performance-reducing threats - Zhao, Wanxiao; Wang, Chengyuan; Wan, Liang; Wang, Qiong; Luo, Biao (Journal of Business Economics and Management, 2021)
A great deal of research attention has been devoted to studying the effects of customer concentration on firm strategic acts. Scholars have also investigated the relationship between customer concentration and firm innovation, but concluded inconsistent findings of such relationship. Furthermore, the underlying mechanism remains unclear. To address these concerns, this study decouples exploratory innovation from firm innovation and introduce performance-reducing threats perceived by the executives as the mediator. Based on the observations of China high-tech listed firms from 2011 to 2018, empirical results show that customer concentration has a U-shaped relationship with exploratory innovation, via the mediating effect of performance-reducing threats perceived by the executives.